Household Waste Management in Increasing Economic Capacity Based on Bioconversion and Circular Economy in Putrapinggan Village, Pangandaran Regency, West Java - Dian Kurniawan; Noneng Masitoh; Dede Arif Rahmani; Sakifah Sakifah (Warta Pengabdian Andalas, 2024)
The Lecturer Team from Economics and Business, Siliwangi University, conducted Community Service Activities (PPM) for the youth and PKK groups in Putrapinggan Village, Pangandaran Regency, in May 2023. The engagement service had the theme of applying science and technology, which aims to transfer knowledge and technology from experts in household waste management in organic and inorganic waste based on bioconversion and a circular economy. Problems encountered after discussions with partners can be identified, such as partner problems in handling household waste that need to be correctly optimized. This PPM was carried out using training methods and mini-workshops, mentoring, strengthening, and collaboration, which were carried out continuously. Organic waste management utilized bioconversion technology from Black Soldier Fly (BSF) maggots. Meanwhile, socializing the application of circular economy principles in the form of the principles of reduction, reuse, recycling, recovery, and repair was an effort that the team can make to the community to support government programs in efforts to handle sustainable inorganic waste. The implementation of this service has had a direct impact in the form of increasing residents' insight regarding waste handling literacy, increasing awareness and concern regarding household waste management, and indirect impacts, namely improving health levels and increasing residents' economic capacity.